EEFFECTS OF THE BAREH RANDANG WITH DADIH ADDITION ON TOTAL CHOLESTEROL LEVELS AND BODY WEIGHT IN HYPERCHOLESTEROLEMIC WISTAR RATS - Lastrie Asrya; Waisaktini Margareth; ST. Austa Nusra; Azzahra Nur Fadhilah; Restu Sakinah; Rozaliny Asri (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Background: Hypercholesterolemia is a condition of elevated total cholesterol ≥240 mg/dl, triglycerides ≥150 mg/dl, and LDL ≥160 mg/dl, accompanied by decreased HDL <40 mg/dl, making it one of the triggers of coronary heart disease and atherosclerosis. This condition can be controlled by managing a healthy and balanced diet, one of which is by consuming functional food in the form of bareh randang with added dadih. It contains lactic acid bacteria that function to inhibit the growth of pathogenic bacteria while lowering high blood cholesterol levels. Purpose of the study: to determine the effect of administering bareh randang with added dadih on the reduction of total cholesterol levels and body weight in hypercholesterolemic wistar rats. Research method: true experimental with a pre-post intervention only randomized control group design. This study involved 36 hypercholesterolemic male wistar rats aged 12 weeks and weighing 200 g, which were then divided into 4 groups: control (standard feed); P1 (standard feed + bareh randang); P2 (standard feed + dadih); and P3 (standard feed + bareh randang dadih) at a dose of 3.7 g/day. The intervention was administered for 14 days. Differences between treatments were tested using a paired t-test, while differences among groups were tested using One-Way Anova at a confidence level of α=0.05, followed by the Tukey test. Results: A significant reduction in total cholesterol levels occurred only in groups P2 and P3 (p<0.05), whereas groups K and P1 showed no meaningful reduction. Group P3 experienced the highest reduction in total cholesterol, at 31.07%, accompanied by an increase in body weight of 44.3 ± 3.69 g.